PENYELESAIAN SENGKETA HUBUNGAN INDUSTRIAL DALAM PEMUTUSAN HUBUNGAN KERJA (PHK) MENURUT SISTEM PERADILAN DI INDONESIA DENGAN MALAYSIA: Settlement of Industrial Relations Disputes in Termination of Employment According to the Judicial System in Indonesia and Malaysia - Rizky, Normalita; Yurikosari, Andari (Faculty of Law, Universitas Trisakti, 2024)
Industrial relations conflicts are intricate issues that often arise in the lives of individuals, particularly for those in worker and employer roles. These conflicts can lead to employment termination or layoffs. Each country has its own methods for resolving labor disputes depending on the adopted legal system. Indonesia uses a Civil Law system, while Malaysia follows a Common Law system, resulting in different approaches to resolving these conflicts. This study aims to examine and describe the impact and resolution efforts related to labor disputes in both countries. The research methodology employed is normative legal research, with a descriptive analytical approach. Primary data, obtained from interviews, and secondary data, obtained from literature studies, were used for analysis. The study reveals notable disparities in labor dispute resolution between the two countries, particularly in the process and the role of judges during dispute resolution hearings.